Synthesis and characterisation of transition metal complexes of schiff bases derived from dithiocarbazate and application of these complexes as cyclohexane oxidation catalysts - Alshaheri, Ali Ahmed Qaid (2019)
Schiff bases and their complexes are excellent applicants’ compounds that are synthesized by the condensation of a primary amino compound with either ketones or aldehydes for a variety of industrial applications. They can act as catalysts for the catalytic oxidation of organic compounds. In recent years, most of the researches in oxidation catalysis focused on how to employ the metal complexes-catalyzed oxidation of organic compounds. Schiff base complexes of transition metals can be used for catalytic oxidation of hydrocarbons in the presence of tert‑butyl hydroperoxide (TBHP) and hydrogen peroxide. The oxidation of cyclohexane is an important oxidation reaction for industrial applications as their products, cyclohexanone and cyclohexanol, also known as K-A oil, are very important to produce nylon 6,6 and nylon-6 polymers, plastics, lubricant additives, fibers and are intermediate for pharmaceuticals. In this work, dithiocarbazate Schiff bases derived from the condensation of S-methyldithiocabazate (SMDTC) and S-benzyldithiocarbazate (SBDTC) with 2,6-diacetylpyridine (diAP) and 1,3-diacetylbenzene (diAC), and their Ni(II), Cu(II), Fe(II), Co(II), Mn(II) and Zn(II) complexes have been successfully synthesized in ethanol and characterized using several physico-chemical techniques. The oxidation of cyclohexane by the prepared metal complexes as catalysts has been investigated in the presence of tert‑butylhydroperoxide (TBHP) and hydrogen peroxide as the oxidative source under mild conditions at 4h, 70°C, 0.09 mmol catalyst and 20 mmol oxidant. The product was analyzed using gas chromatography and it was found that cyclohexanol and cyclohexanone are the main products for the oxidation reaction. All the transition metal complexes of the Schiff bases showed activity toward oxidation of cyclohexane. Time of the reaction, temperature, and the concentration of TBHP and catalyst influenced the selectivity and conversion of the cyclohexane oxidation. The complex, [CuSBdiAC], was found to be the most active catalyst with ~50% conversion.